Management of patients with clinically suspected pyelonephritis in a resource poor setting - Weerasekera, M.; Fernando, N.; Welgamage, T.; Premarathna, K.; Wijesuriya, T.M.; Ranasinghe, N. (Journal of the Ceylon College of Physicians, 2015)
Attached
Keywords: pyelonephritis; gentamicin; uropathogens; Sri Lanka